Interventions to Reduce Bullying and Cyberbullying - Wong, Dennis (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book, a Special Issue of the International Journal of Environmental Research and Public Health, has been curated by three leading international experts on the topic. Following their editorial, there are 14 contributions on the topic of interventions against bullying, including cyberbullying, and similar abusive behaviors such as dating violence. Some contributions also assess positive or protective factors such as well-being, self-efficacy, and school climate. Eight of the contributions directly assess the effects of an intervention, with pre/post test designs and experimental and control groups. The other contributions examine a range of relevant topics, such as teacher attitudes and pupils' confidence in intervening rather than being passive bystanders. Ten countries are represented among the authors. Most of the articles are about secondary schools (pupils, or teachers), but there are also contributions on early childhood, primary school, and university. This book will be of interest and relevance not only to researchers but also to teachers and educational practitioners concerned with pupil safety and well-being in school, and provides practical ways to reduce bullying and its harmful effects.